2012
DOI: 10.1016/j.foodcont.2012.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Daily intake estimates of fumonisins in corn-based food products in the population of Parana, Brazil

Abstract: a b s t r a c tOne hundred (100) samples of corn-based food products were collected between February 2007 and July 2010 to estimate the intake of fumonisins in the state of Paraná, Brazil. The identification of fumonisins was performed by high-performance liquid chromatography with fluorescence detection and post column o-phthaldialdehyde (OPA) derivatisation. The occurrences of fumonisins B 1 (FB 1 ) and B 2 (FB 2 ) were 82% and 51%, respectively, with concentrations ranging from 126 to 4348 mg/kg (FB 1 þ FB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 21 publications
2
32
0
7
Order By: Relevance
“…In other studies fumonisins were present in 50% of cornflake samples (2/4), and the mean value was 30.5 µg/kg [26]. In Martin's et al studies, cornflakes showed significantly higher contamination by fumonisins, where the average values of B 1 and B 2 were 341 µg/kg and 87 µg/kg, respectively [24]. Bryła et al analyzed 19 samples of cornflakes, from which nine were contaminated by B 1 and B 2 in the range of 13 to 248 µg/kg [27].…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…In other studies fumonisins were present in 50% of cornflake samples (2/4), and the mean value was 30.5 µg/kg [26]. In Martin's et al studies, cornflakes showed significantly higher contamination by fumonisins, where the average values of B 1 and B 2 were 341 µg/kg and 87 µg/kg, respectively [24]. Bryła et al analyzed 19 samples of cornflakes, from which nine were contaminated by B 1 and B 2 in the range of 13 to 248 µg/kg [27].…”
Section: Resultsmentioning
confidence: 88%
“…The analyzed samples of corn grits were free from contamination with B 2 (Table 2). Martins et al observed fumonisins in 19 samples of corn grits (67.9%), where high levels of B 1 and B 2 were found in concentrations ranging from 91 to 3,462 μg/ kg and from 45 to 886 μg/kg, respectively [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusarium verticillioides e F. proliferatum são os principais produtores de fumonisinas, os quais possuem elevada ocorrência em milho e seus derivados (FIGUEIRA et al, 2003). O milho (Zea mays L.) possui elevado valor nutricional constituindo um produto básico de consumo humano (MARTINS et al, 2012). A produção anual de milho no Brasil girou em torno de 53 milhões de toneladas na safra de 2009/2010, sendo o terceiro maior produtor mundial do referido grão (MAPA et al, 2015).…”
Section: Introductionunclassified
“…A produção anual de milho no Brasil girou em torno de 53 milhões de toneladas na safra de 2009/2010, sendo o terceiro maior produtor mundial do referido grão (MAPA et al, 2015). Estudos realizados anteriormente no Brasil demonstraram a elevada incidência de contaminação por fumonisinas no milho e derivados, chegando a 100% de incidência em alimentos comercialmente disponíveis SCUSSEL, 2004;BITTENCOURT et al, 2005;MARTINS et al, 2012).…”
Section: Introductionunclassified